A Preliminary Report on Archaeological Investigations at the Danish Plantation Settlements along the Sotu Akuapem Ridge, Ghana - Y. Bredwa-Mensah; L. Crossland (Papers from the Institute of Archaeology, 1997)
This is a report on archaeological surveys and excavations jointly directed by the authors, carried out as part of the Slavery and the Danish Plantations Project, funded by the Senior Members Research Grant of the University of Ghana, Legon.
Keywords: slavery; Excavation